Assessing the Role of Family Support in Heart Failure Care: A Quantitative Perspective - Alsa Cicin Sejatika; Beti Kristinawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Heart failure causes functional impairment and impacts patients' quality of life. A family-centered approach involving families as partners in care is an effective strategy for improving patients' quality of life. Objective: This study aims to identify the role of families in implementing family-centred care for heart failure patients. A quantitative descriptive design involving 317 families of heart failure patients. Purposive sampling based on predetermined criteria was applied in this study. The Family Centered Care Assessment of Family (FCCA-F) instrument was used to identify the role of families in decision-making, providing support, and family-to-family and peer support. Data analysis was performed using computer software. Analysis to present data used descriptive statistics. The results showed that the domain of the role of families in decision-making and the support provided by the immediate family were